Reconstruction of subsurface structure from ambient seismic noise: An example from Ketzin, Germany - Xu, Z.; Juhlin, Christopher; Gudmundsson, O.; Zhang, F.; Yang, C.; Kashubin, A.; Lüth, S. (2012)
Passive seismic interferometry is a new promising methodology for seismic exploration. Interferometry allows information about the subsurface structure to be extracted from ambient seismic noise. In this study, we apply the cross-correlation technique to approximately 25 hr of recordings of ambient seismic noise at the Ketzin experimental CO 2 storage site, Germany. Common source gathers were generated from the ambient noise for all available receivers along two seismic lines by cross-correlation of noise records. This methodology isolates the interstation Green's functions that can be directly compared to active source gathers. We show that the retrieved response includes surface waves, refracted waves and reflected waves. We use the dispersive behaviour of the retrieved surface waves to infer geological properties in the shallow subsurface and perform passive seismic imaging of the subsurface structure by processing the retrieved reflected waves. © 2012 The Authors Geophysical Journal International © 2012 RAS.